Issues of discrepancy between the original and ostensible from the book of inheritance by collection and study - Altayyar, Alaa Ahmad (Journal of Islamic Sciences, 2021)
The research aims to collect issues that contradict the origin and the apparent mentioned in the chapter on the obligations, and study them in a comparative jurisprudential study that shows the position of the original, the apparent position and the face of the contradiction, and then weighting one of them with the evidence, and the method used in the study is the inductive and deductive approach. The most important findings of the study is that: There may be a conflict between origins and ostensible such as evidence and the weights in which the conflict occurs, according to the human view, not according to the fact of the matter, because religion does not conflict, if we find that there is a conflict between us, we collect the original and pure and face the conflict even We remove what appeared to us from conflict, it is required to implement the issue three conditions: the union of origin and ostensible in her , and the realization of the conflict between the origin and the apparent, and the difference in the time of the occurrence of the origin and the apparent, and I can not say that the issues i collected are all issues that conflict the origin and the ostensible in these sections, but they are what I have reached by reading, research.